"I don't know why I am in hospital": amnesia in non-fatal hanging. Issue 11 (November 2021) - Arafat, S.M. Yasir; Karim, A.K.M. Bazlul
Abstract: There is an extreme dearth of empirical studies assessing the neuropsychiatric outcome of non-fatal hanging that indicates little attention to the area has been paid. We aimed to report the memory disturbances of 14 cases after an immediate non-fatal hanging attempt. We conducted the study from August 2020 to June 2021 and collected data from 14 hospitalized patients after an immediate non-fatal hanging attempt. We conducted series of clinical examinations to assess the memory disturbance and recorded it. Among the 14 cases, four (28.8%) were males and the rest ten (71.2%) were females. The mean age of the cases was 25.28 ± 8.19 years ranging from 15-40 years. All the cases had retrograde amnesia while six (42.9%) had both anterograde and retrograde amnesia. The current pilot study reported the distribution of memory disturbances among fourteen cases of non-fatal hanging that adds preliminary findings to the under-researched area and warrants further empirical studies to generalize the study results. Abstract : Non-fatal hanging; Amnesia; Retrograde amnesia; Anterograde amnesia; Suicide in Bangladesh.